Mechanistic analysis of aliphatic β-lactones in Vibrio harveyi reveals a quorum sensing independent mode of action. Issue 80 (19th September 2016) - Zhao, Weining; Lorenz, Nicola; Jung, Kirsten; Sieber, Stephan A.
Abstract : β-Lactone analogs of autoinducers potently inhibit Vibrio harveyi bioluminescence using a quorum sensing independent mechanism interfering with fatty acid biosynthesis. Abstract : N -Acylhomoserine lactones are autoinducers of quorum sensing (QS) in Gram-negative bacteria. We exploit here the role of structurally related β-lactones in the inhibition of Vibrio harveyi bioluminescence and identify a derivative with nanomolar potency. Surprisingly, QS was not affected and combined proteomic/biochemical studies revealed insights into the cellular mode of action.